The Dynamics of Identity Politics Polarization in the 2017 Jakarta Gubernatorial Election - hudianto, huwaidatul izza (Journal of Political Islam, 2025)
ABSTRACT Identity politics has become an important element in the ongoing political dynamics of Indonesia, especially following increased social tensions and polarization during the general elections. This refer to the use of identities that are based on commonalities such as religion, ethnicity, or culture. In this context, s are used as the basis for political mobilization. Anies Baswedan has become a central figure often associated with symbols of certain identities, particularly since the 2017 Jakarta gubernatorial election and the 2024 general election. This study aims to analyze how public communication can shape, produce, and reinforce the identity politics of Anies Baswedan’s portrayal, as well as how this plays a role in political polarization in Indonesia. This study uses a qualitative approach with a case study method to analyze in depth the complex socio-political phenomena from various political texts, media reports, speeches, and media posts during the period 2017-2024. The results of the study show that Anies Baswedan is constructed on his strong identity narrative, reflecting tensions between majority and minority groups, conservatives and progressives. The media and political actors also play a very important role in directing this discourse for ideological and electoral interests. These findings confirm that identity politics, when influenced by public discourse, will deepen social fragmentation and could also threaten the integrity of democracy in Indonesia.